Nitrogen-doped micropores binder-free carbon-sulphur composites as the cathode for long-life lithium-sulphur batteries - Yao, Yuechao; Liu, Peng; Zhang, Qi; Zeng, Shao-Zhong; Chen, Shuangshuang; Zou, Guangjin; Zou, Jizhao; Zeng, Xierong; Li, Xiaohua (Elsevier, 2018)
Nitrogen-doped micropores-contained carbon nanofibres (NMCNFs) were prepared by carbonizing ZIF-8 grown in liquid-phase along with electrospinning. When NMCNFs act as sulphur host materials in lithium–sulphur batteries, NMCNFs can retard the shuttle effect and dissolution of polysulfides through the synergic action of effective physical confinement to micropores and nitrogen surface chemical absorption. NMCNFs show a capacity up to 636 mAh g−1 after 500 cycles against Li anode.
Keywords: Carbon materials; Energy storage and conversion